Informality and minimum wages by cohort in Colombia (2014)
This article aims to analyze the effect of minimum wage levels on the decision to join the informal job sector. We estimated a pseudo panel model of engagement in the informal sector using an IV-probit. Our results show that an increased wage gap-the relative difference between observed and minimum wage-has not only a disincentive effect on the probability of joining informality, but also leads to a substitution effect between younger and older cohorts.